Harnessing genetic resistance to rusts in wheat and integrated rust management methods to develop more durable resistant cultivars - Mapuranga, Johannes; Zhang, Na; Zhang, Lirong; Liu, Wenze; Chang, Jiaying; Yang, Wenxiang (Frontiers in Plant Science, 2022)
Wheat is one of the most important staple foods on earth, and it is grown worldwide. Wheat rust is a vital disease that have long been a source of worry for wheat breeders and farmers. Utilization of resistance cultivars is the most effective and economic means to control the disease. More than 200 resistance genes were found from common wheat and wheat wild relatives by conventional techniques and molecular biology techniques, and a large number of wheat rust resistant varieties were bred in the recent 100 years. Virulence against rust resistance genes in wheat is enhanced by mutation and selection to develop new rust races. Due to the emergence of severe pathotypes of these rusts, they have presented systematic risks to the spread of an epidemic. In the long struggle between wheat and rust, how wheat can effectively resist the infection, expansion of rust and the yield losses caused by rust is one of the hot spots in plant pathology researches. This review will focus on a high-level overview of the advances in understanding the mechanisms of wheat resistance against rusts and the future perspectives. It also explores the molecular basis of the interactions between rust pathogens and wheat.